Standardization of MSME Timber in Tanjung Jaya Village - Goenadhi, Felix; Rahmiati, Filda; Prayoga, Tasya Zahwa; Wagino, Azzah Al-afnan (AIBPM Publisher, 2023)
As one of the villages in the Panimbang Regency, Tanjung Jaya Village provides some promising business potential, especially timber artisan. However, this business opportunity has not been fully utilized by the people of Tanjung Jaya and MSME actors. Therefore, this program aims to develop strategies regarding the standardization of MSMEs Timber professionally and independently to support income and improve the welfare of the people in Tanjung Jaya Village. The implementation method used is interviews with MSME actors. First, the researcher asked MSME actors in Tanjung Jaya Village about managing a business professionally, innovatively, creatively, and independently. Next, researchers will score and triangulate the results of interviews with the Tanjung Jaya community to carry out MSME development strategies. Implementing these activities positively impacts the people of Tanjung Jaya Village to increase business potential, especially in the MSME sector. In the end, this program can support income, improve the welfare of Tanjung Jaya Village's people, and contribute to increasing economic growth in Panimbang Regency.